2012
DOI: 10.1097/qai.0b013e31826be75e
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Timing of Antiretroviral Treatment Initiation Based on Monitoring CD4 Counts

Abstract: Objective To evaluate factors affecting antiretroviral therapy (ART) start time when triggered by a CD4 count < 350 cells/μl while monitoring counts over time. Measurement frequency, requirement for confirmatory counts, and precision and accuracy of CD4 enumeration technology were considered. Methods Using a model of CD4 count trajectories among seroconverters in the Multicenter AIDS Cohort Study, sequences of counts were simulated for a large hypothetical population monitored for 5 years from seroconversion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…We compare different models based on observed/predicted plots, normal QQ-plots, and residual plots (see Appendix), as well as the simplicity of the model and its interpretation. We find that a √ z ij -transformation of CD4 provides satisfactory results since it produces similar results as the log-transformation and it is widely used in the analysis of datasets from the AIDS Clinical Trials Group network (ACTG) (see, e.g., Noubary and Hughes 2012).…”
Section: Models For Viral Load and Cd4 During Artmentioning
confidence: 95%
“…We compare different models based on observed/predicted plots, normal QQ-plots, and residual plots (see Appendix), as well as the simplicity of the model and its interpretation. We find that a √ z ij -transformation of CD4 provides satisfactory results since it produces similar results as the log-transformation and it is widely used in the analysis of datasets from the AIDS Clinical Trials Group network (ACTG) (see, e.g., Noubary and Hughes 2012).…”
Section: Models For Viral Load and Cd4 During Artmentioning
confidence: 95%
“…Recent reports have shown that random fluctuations in CD4 count correlate with fluctuations in total lymphocyte count [15]. Abnormally high or low lymphocyte counts caused by factors other than HIV can produce elevated or depressed CD4 counts that are not representative of between the PointCare NOW and FACSCalibur in classifying results as being highly likely to indicate initiating ART, highly likely to indicate not initiating ART, and requiring a near-term repeat measurement to rule out normal day-to-day fluctuations in patient CD4 count [9][10][11].…”
Section: Classification Agreementmentioning
confidence: 99%